INTEGRATED TWIN TOWER PRADIGMA IN CONTEMPOREARY HIGHER EDUCATION ISLAMIC RELIGION - Al Fitri, Qurrota; Diana, Alfi Elma; Assegaf, Abd Rachman; Alfarizi, Muhammad Salman (IAIN PAREPARE, 2024)
In facing modern developments, universities are required to carry out innovative learning designs and processes in order to produce graduates who are able to compete with the demands of the times. The purpose of writing this article is to examine the Islamic Religious Education (PAI) policy in higher education and its development based on the Twin-Tower paradigm. The author uses the library research method to answer the problem formulation that has been formulated. The data analysis technique includes three steps, namely data condensation, data presentation and drawing conclusions. The results of this paper show that the State Islamic University (UIN) Sunan Ampel Surabaya applies the Twin Tower paradigm in the development of Islamic Religious Education (PAI), which emphasizes integration between religious knowledge and general knowledge. This paradigm aims to create graduates who not only have a deep understanding of religious knowledge, but also competence in the fields of science and technology. The Islamic religious education curriculum at UIN Sunan Ampel was developed in accordance with the guidelines set by the government with an integrative multidisciplinary approach based on the twin tower concept. The strategy implemented by the PAI study program includes integrating the religious science curriculum with modern technology. Through a multidisciplinary approach, the curriculum is designed to meet the needs of society and answer the challenges of the times, with the aim of producing a generation of ulul albab who have intellectual, spiritual intelligence and good character.